2002
DOI: 10.1038/sj....bjc.6600211...
|View full text |Cite
|
Sign up to set email alerts
|

The presence of bone marrow cytokeratin-immunoreactive cells does not predict outcome in gastric cancer patients

Abstract: The independent prognostic significance of isolated tumour cells in bone marrow is still a matter of debate. This study evaluated the possible association of bone marrow micrometastases with tumour progression and prognosis in patients affected by gastric cancer. Bone marrow aspirates from both iliac crests were obtained from 114 consecutive patients operated on for gastric cancer. The specimens were stained with monoclonal antibody CAM 5.2 which reacts predominantly with cytokeratin filaments 8 and 19. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…To our knowledge, this was the largest clinical study to examine BM micrometastasis of gastric cancer. CK2 has been commonly used for detecting micrometastasis in human gastrointestinal cancer, although recent data have shown that CK protein expression is down (Koch et al 2005;Weitz et al 1999;Slade et al 1999;Champelovier et al 1999;Matsunami et al 2003;Kakeji et al 1999;Macadam et al 2003;de Manzoni et al 2002). Although only 24 samples were examined, it became clear that both immunostaining and PCR showed very similar results.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…To our knowledge, this was the largest clinical study to examine BM micrometastasis of gastric cancer. CK2 has been commonly used for detecting micrometastasis in human gastrointestinal cancer, although recent data have shown that CK protein expression is down (Koch et al 2005;Weitz et al 1999;Slade et al 1999;Champelovier et al 1999;Matsunami et al 2003;Kakeji et al 1999;Macadam et al 2003;de Manzoni et al 2002). Although only 24 samples were examined, it became clear that both immunostaining and PCR showed very similar results.…”
Section: Discussionmentioning
confidence: 78%
“…Some studies showed that patients with micrometastasis had a signiWcantly worse survival rate than those without micrometastasis and a signiWcant correlation between the depth of invasion and micrometastasis (Maehara et al 1996a;Ishigami et al 2003;Yasuda et al 2002;Choi et al 2002). However, there are not many reports of micrometastasis of gastric cancer to the BM (Oki et al 2002;Maehara et al 1996b;Matsunami et al 2003;Kakeji et al 1999;Macadam et al 2003;de Manzoni et al 2002). We previously reported that cytokeratin-positive cells were detectable in the bone marrow of gastric cancers and that the microvessel density in the primary tumor doubly exceeded that of the cytokeratin-positive tumors, in comparison to Wndings in the negative tumors.…”
Section: Discussionmentioning
confidence: 93%
“…The independent prognostic value of BM MMs has not been confirmed in all studies [68,79,82] and most of the published data are difficult to compare and interpret. Significant methodological differences, including the use of different detection methods, variable antibodies and staining procedures, study design and setting of the cutoff points seem to confound the evaluation of the otherwise impressive body of evidence favoring the prognostic value of MMs.…”
Section: Prognostic Value and Clinical Impact Of Mmsmentioning
confidence: 88%
“…The prognostic value of MMs has been investigated in several previous studies comprising patients with epithelial cancers such as breast [67][68][69][70][71][72][73][74][75][76], colorectal [45,[77][78][79], gastric [80][81][82], esophageal [83][84][85][86], lung [87][88][89], ovarian [90,91], cervical [92][93][94], prostate [95], pancreatic or ampullary [96,97], as well as other forms of carcinoma, with variable results (Table 1). Among these tumors breast cancer is the most extensively studied, mostly because it is more frequently associated with late recurrences.…”
Section: Prognostic Value and Clinical Impact Of Mmsmentioning
confidence: 99%
“…The prognostic implications of ITC in patients with tumours of the gastrointestinal tract are controversial. In gastric cancer, ITC in the bone marrow were either significantly associated with overall survival (Jauch et al, 1996), disease-free survival (Gretschel et al, 2006), or were devoid of any prognostic value (de Manzoni et al, 2002). However, the presence of ITC is interesting not only from the prognostic point of view, but also for their potential predictive value.…”
Section: Discussionmentioning
confidence: 99%